A pedagogical and political transformation in context: the relationship between a regular school and a specialized educational service center - Bárbara Martins de Lima Delpretto; Bianca Campos Carlos dos Santos (Universidade Federal de Santa Maria (UFSM), 2013)
On the assumption that regular institutions and specialized educational service centres operate in specialized educational service mandatory bid for students target audience of special education, they must establish a relationship capable of facilitating the process of education of these students (MEC, 2008, 2009, 2010). Therefore, this article aims to report an investigation on the relationship between a regular school education with the registration of students with disabilities in basic education and an institution that offer specialized educational service, understanding the role of each professional in the education of a student with disabilities in the city of São Carlos (SP). The methodology is the case study with use of questionnaire (GIL, 1999). Regarding the preliminary conclusions from previous observation, it is understandable that the proposals of both institutions are cohesive to organizational management adopted by each one. However, regarding the execution of projects that require communication beyond the institution, we see that these have not been effectively implemented to the specificities of the students, in order to leverage their capabilities.